Impact of Japan’s Aging Population on Healthcare Costs and the Long-Term Care Insurance System - Vale Haward (Studies in Social Science & Humanities, 2024)
Japan’s demographic landscape is rapidly changing, leading to an unprecedented increase in the aging population. This demographic shift presents significant challenges for the healthcare system, particularly in escalating healthcare costs and the sustainability of the Long-term Care Insurance (LTCI) system. This paper examines the impact of these demographic changes on healthcare costs and evaluates the current LTCI system’s ability to meet the increasing demand for elderly care services. Through a thorough review of existing literature, demographic data analysis, and policy evaluation, this study proposes strategic recommendations to ensure the sustainability and effectiveness of Japan’s healthcare system in the face of an aging society.